History of the paleontological research in the Araripe basin, Northeast Brazil - Carvalho, Marise Sardenberg Salgado de; Santos, Maria Eugenia C. Marchesini (Anuário do Instituto de Geociências, 2005)
The Araripe Basin is located in Northeastern Brazil and is known by its diversified Cretaceous fauna and flora. The great scientific valuable fossils as insects, plants, mollusks, fishes and pterosaurs are represented mainly in Santana Formation layers. This paper displays a historical research made on the Araripe Basin since the 19 century.